STUDY ON PROCESSING OF DRIED CHILI INTO BLOCK CHILI - Khaeruddin Hidayat; Muhammad Syaiful; Kurnia Herlina Dewi (Jurnal Agroindustri, 2013)
The research objective is to obtain the drying period of various capacities dryer to reach the best moisture content in the process of blocks dried chili production and gaining the consumer acceptance to the product. This study used a completely randomized design (CRD) with two factors: the capacity of the material and the drying time and three times repetition. The measured parameters were changes of weight during drying process, moisture content, organoleptic tests and levels of acidity (pH). The results showed that the drying periods with best moisture in the process of blocks dried chili production are drying for 8 hours at capacity of 0.3 g/cm2, 10 hours at a capacity of 0.5 g/cm2 and 10 hours at a capacity of 1 g/cm2. The highest consumer acceptance to the product for the color, aroma and overall attributes is on the blocks dried chili with a water content of 41-60%, while for the aroma is on the blocks dried chili with a water content of 61-80%.